Ilmu dan Kepentingan Politik Tinjauan Hukum Islam - Rosdalina Bukido; Misbahul Munir Makka; Djihan Magfirah Rivai; Faradila Hasan (Institut Agama Islam Negeri Curup, 2019)
This research made because seeing politics that happened in Indonesia this time, evaluating of it from facet Punish Islam. All political perpetrator which have intellectual as guarantor can develop and also move forward state which we love. Social phenomenon that happened in society that is where all political perpetrator which his science application for the sake of is other, that for the benefit of own, group had. Method used by researcher is descriptive. Result of research indicate that all political perpetrator is science application which they have not for the benefit of society but personal for the benefit of as well as group political perpetrator prefer to give political promise but not coincide. Political so that that happened now, politics which in confusion where private interest taken as especial directive. As a result, development and development of state for the shake of kepentigan of society can not be distributed. If us in Al-Quran that that promise a trust which must be shouldered and all my me, politics now which prefer to break a promise it referred all liar. So that according to writer of political perpetrator ought to more is majoring of promise which he have tell.